Helicobacter pylori Infection Is Not Associated with Non-alcoholic Fatty Liver Disease: A Cross-Sectional Study in China - Fan, Nengguang; Peng, Liang; Xia, Zhenhua; Zhang, Lijuan; Wang, Yufan; Peng, Yongde (Frontiers in Microbiology, 2018)
Background and aim: Helicobacter pylori (H. pylori) infection has been reported to promote the development of a variety of extra-digestive manifestations, including type 2 diabetes, cardiovascular and liver diseases. Recently, the association between H. pylori infection and nonalcoholic fatty liver disease (NAFLD) was also proposed. However, evidence from different studies was controvertial. We therefore performed this study to investigate the relationship between them in a large population of apparently healthy subjects in China. Methods: A total of 21456 subjects underwent a healthy checkup program were included. H. pylori infection was detected by 14C urea breath test (14C-UBT) and NAFLD was diagnosed by ultrasonography. Results: Subjects infected with H. pylori had a more unfavorable metabolic profile, including higher levels of body mass index (BMI), blood pressure, triglycerides (TG) and lower levels of high-density lipoprotein cholesterol (HDL-C) , as compared with those without H. pylori infection (all P < 0.05). Moreover, the prevalence rate of NAFLD was significantly increased in subjects with H. pylori infection when compared with those without H. pylori in women (23.6% vs. 21.5%, P < 0.05), but not in men (46.5% vs. 45.5%, P > 0.05). After adjusting for confounding factors including age, sex, BMI, blood pressure and lipid profiles, multivariate logistic analysis revealed that H. pylori infection was not independently associated with the risk of NAFLD in the total population (OR = 0.9, 95% CI = 0.9-1.0, P = 0.097). Also, subgroup analysis (stratified by age, sex, BMI and diabetes status) showed no independent association between H. pylori infection and NAFLD. Conclusions: Our data suggests that H. pylori infection is not independently associated with the risk of NAFLD in apparently healthy subjects.